Pemuda Sigap dan Tanggap Covid-19 serta Pembentukan Masyarakat yang Berjiwa Spiritual di masa Pandemi - Irna Tri Yuniahastuti; Ina Sunaryantiningsih (Jurnal Pengabdian Pada Masyarakat, 2021)
YOUTHS ARE ALERT AND RESPOND TO COVID-19 AND THE ESTABLISH OF A SPIRITUAL COMMUNITY DURING THE PANDEMIC. The corona virus has become a pandemic that has hit all the world, including Indonesia. Along with the increase in the number of infected victims and the death toll on a national scale due to significant exposure to the virus, everyone becomes anxious and worried, including the residents of the village of Kartoharjo, East Java. Several attempts were made by the community and village officials to prevent transmission of the corona virus. Apart from physical effort, spiritual (inner) work is also carried out. Some of the activities carried out to support these efforts include, a) spraying disinfectants on roads, public places and people's homes, b) distributing basic necessities to the poor and affected, c) holding mutual cooperation markets, d) limiting social activities in outside the home, and e) perform "slametan" refuse logs and prayer together. In addition to these activities, education was also carried out to the public about diligently washing hands, wearing masks, and reducing the intensity of going out of the house aimlessly. With these activities proven to be effective in the spread of the corona virus, in addition, residents can be calm about the problems of life and death in the midst of the pandemic while remaining physically and mentally determined. The goal of this service activity has been achieved, this is evidenced by only 1 citizen who was positive for the corona virus.